ApoptomiRs of Breast Cancer: Basics to Clinics - Sharma, Shivani; Patnaik, Praveen K.; Aronov, Stella; Kulshreshtha, Ritu (Frontiers in Genetics, 2016)
Apoptosis is a highly regulated process, the deregulation of which has been associated with the tumor initiation, progression, metastasis and response to therapy in various cancers including breast cancer. High levels of apoptosis have been correlated to malignant phenotype and worse prognosis in breast cancer. Breast cancer therapy relies on the induction of apoptosis for mediating cancer cell death. Thus, identifying apoptotic mediators and regulators is imperative for molecular biologists and clinicians for benefit of patients. The regulation of apoptosis is complex and involves a tight equilibrium between the pro- and anti-apoptotic factors. Recent studies have highlighted the role of miRNAs in the control of apoptosis and their interplay with p53, the master guardian of apoptosis. However, there has been no report so far that reviews the miRNAs in breast cancer that are involved in the regulation of apoptosis. Here we summarize and integrate the data on the role of miRNAs in apoptosis in breast cancer and the clinical advantage it may offer for the prognosis or treatment of breast cancer patients.